Factors associated with perceived quality in Turkish fitness centres: a qualitative perspective - Sevilmiş,Ali (2022)
Abstract This study aimed to define the general factors affecting the quality of fitness centres from the point of view of the members’ opinions and the relation densities of the features within these factors. The study was carried out using the qualitative method. Data coding was done utilising MAXQDA, a qualitative data analysis program. MAXQDA’s code co-occurrence model feature is employed to visualise code relationships. According to the research findings, the most intense relationship that the factors affecting the staff quality perception of fitness centres have with each other was defined as “Willing to help-Friendliness”. When looking at the results obtained in other factors, codes of “Expertise-Communication” for the quality of the trainer, “Facility Atmosphere-Air conditioning” for the quality of the physical environment, and “Meeting the need-Program variety” for the program quality were associated with each other. Findings from this study provide implications for facility managers who need to closely monitor fitness centres’ physical environment, staff, instructors, program quality and implement remedial measures as needed.